TRADISI MENGHAFAL HADIS DI PESANTREN AL-FATAH, TEMBORO KARAS MAGETAN (Analisis Fenomenologi) - dan Hisbulloh Hadziq, Khamim (UNIVERSUM, 2018)
This article describes hadith memorizing tradition in pesantren Al-Fatah, Temboro, Karas Magetan, by studying the motive, purpose, and urgency of hadith memorization (tah}fi>z} al-H{adi>th) in the pesantren. This study employes qualitative research through phenomenology approach to understand the phenomena, especially the attitude and the experience of the pesantren’s community related to research and hadith memorization. In collecting the data, this study uses interview, observation, and documentation. Interview is used to explore data about the process, motive, and the purpose to be achieved in hadith memorizing in the pesantren Al-Fatah Temboro Karangrejo Magetan. Interview is done to teacher, kyai, and students involved in hadith memorizing program. Observation is done by observing directly in the learning process of hadith study included hadith memorizing. Then documentation is used to collect the data and documents related to the result of hadith memorizing. The findings show that the activity of hadith memorizing in the pesantren Al-Fatah has some motives namely to make students have common interaction with the Prophet’s hadith and to strengthen the basic argument with hadith. However, the use of memorization in understanding hadith to solve law problems is not practiced yet. The urgency is more on the strengthen of hadith reference from the main source of hadith based on the memorization. Keywords; the Prophet’s Hadith, tah}fi>z} al-h{adi>th, phenomenology